Entreprenøren som figur under neoliberalismen - Kapitalisme, individ og velfærdsorganisering - Li Langergaard, Luise (Slagmark - Tidsskrift for idéhistorie, 2020)
The article explores the central role of the entrepreneur in neoliberalism. It demonstrates how a displacement and a broadening of the concept of the entrepreneur occur in the neoliberal interpretation of the entrepreneur compared to Schumpeter’s economic innovation theory. From being a specific economic figure with a particular delimited function the entrepreneur is reinterpreted as, on the one hand, a particular type of subject, the entrepreneur of the self, and on the other, an ism, entrepreneurialism, which permeates individuals, society, and institutions. Entrepreneurialism is discussed as a movement of the economic into previously non-economic domains, such as the welfare state and society. Social entrepreneurship is an example of this in relation to solutions to social welfare problems. This can, on the one hand, be understood as an extension of the neoliberal understanding of the entrepreneur, but it also, in certain interpretations, resists the neoliberal understanding of economy and society.